Pemanfaatan Media PARUMA Digital dalam Inquiry Learning untuk Meningkatkan Keterampilan Menulis Pengumuman Siswa Sekolah Dasar - Anastasia Jevis Elrika; Lintang Kironoratri; Fitriyah Amaliyah (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aimed to examine changes in elementary school students’ announcement writing skills after the implementation of the Inquiry Learning model assisted by PARUMA Digital media. The study was conducted based on the need for innovative learning approaches to support students in identifying announcement elements, organizing text structures, and presenting information clearly and systematically.Methods – This study employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The participants were 16 fifth-grade students at SD Kayuapu selected through saturated sampling. Data were collected through announcement writing performance tests administered before and after the learning activities. The data were analyzed using the paired-samples t-test and N-Gain analysis Findings – The results showed a significant pre–post difference in students’ announcement writing scores after participating in learning activities using the Inquiry Learning model assisted by PARUMA Digital media (p < 0.05). The average score increased from 13.69 in the pretest to 16.75 in the posttest. The average N-Gain score was 0.5260 or 52.60%, which was categorized as moderate. Improvements occurred across all writing indicators, with the highest gains observed in identifying announcement elements and organizing announcement structures.Research Implications – The findings indicate that the integration of the Inquiry Learning model and PARUMA Digital media was associated with changes in students’ announcement writing skills within the context of fifth-grade students at SD Kayuapu.